On Politics in Comparative and International Higher Education - Oleksiyenko, Anatoly (Revista Española de Educación Comparada, 2021)
This paper draws attention to key conundrums facing researchers of comparative and international higher education in the age of post-truth and resurgent authoritarianism. The analysis focuses on three salient concerns: world class-universities and academic freedom; power brokerage in the internationalisation of higher education; and challenges of intellectual leadership – that dominated research agendas in the field. Situated at the crossroads of major arguments in the literature and observations derived from academic praxis in the three areas, the critique sets out to explain how politics have been gaining more weight in the construct of comparative and international higher education at a time when corporate elitism is on the rise and the freedoms of inquiry and communication are declining. The study warns about the failures of integrity in this context, and manifests imperatives for safeguarding academic freedom and critical research in the field.